Phenomenological Inquiry of The Lived Experience of People Living with Breast Cancer - Hernan Buena; Marion Jonah Salamanque; Jessa Reyes (Camarines Sur Polytechnic Colleges, 2024)
This phenomenological study sought an in-depth understanding of the lived experiences of people living with breast cancer within the context of their day-to-day lives and the emotional burden brought by the disease and analyzed the data using phenomenological methods. A purposive sampling method was used to determine the number of required participants by interviewing women with breast cancer who will meet the inclusion criteria until the data are saturated and no new topics are generated. A total of six (6) women with breast cancer were interviewed. There are two major themes that emerged and describe the lived experiences among patients with breast cancer. These were varied views of people regarding breast cancer and the importance of the support group to a person, especially in overcoming the challenges and difficulties as they go along their journey of beating breast cancer. In conclusion, by using an in-depth interview, this study found out that the experiences of women who were diagnosed with breast cancer have completed the treatment and some have recurrence and ongoing treatment. Also, there is support received from her family, friends, and co-members, which helps them to overcome and cope with stress, especially the treatment. Through early detection, it plays a vital role in managing Breast Cancer. With proper information dissemination and awareness with regards to breast cancer, this could prevent it from late detection, and early management. However, with regard to early detection, they didn't seek immediate care; rather, they preferred to self-medicate and seek after it worsens.